Clinical characterization, disability, and mortality in people with strokes during 90 days - Mariana de Almeida Moraes; Fernanda Carneiro Mussi; Ludmila Santos Muniz; Elieusa e Silva Sampaio; Tatiana de Sena Leitão; Carlos Antônio de Souza Teles Santos; Pedro Antônio Pereira de Jesus (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to describe clinical characteristics and mortality of people with ischemic cerebrovascular accidents (strokes); to compare disability before the event and 90 days after. Methods: longitudinal study with 308 people hospitalized in Salvador-BA. Data collection took place from 03/2019 to 01/2020. Descriptive and inferential statistics were used. Results: mean age was 64.8 years, and National Institute of Health Stroke Scale score was 10.7. The median length of stay in the hospital was 11 days. Afro-descendants predominated (84%), elementary educational level (68.4%), income up to three minimum wages (89.1%), arrival within 4.5 hours of symptoms (57.9%) and admission to a specialized unit (71.8%). Prevalence of thrombolysis: 26%. The asymptomatic before the event category predominated (85.3%) as did the moderate/severe disability (41.5%) after 90 days. 19.7% of the sample evolved to death. Conclusions: the high mortality and disability generated by the event have implications for health management and care.